2019
DOI: 10.2478/bhk-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

The level of moral competences of pre-service PE teachers – a reason to worry?

Abstract: Summary Study aim: The main purpose of this study was to examine the level of moral competences of 437 pre-service physical educa­tion (PE) university students. It was also designed to evaluate the level of moral competency and the correlations with factors (i.e. Parents, Religion, School education, PE teacher, Sport coach, Studies, Media and Peers) potentially influencing moral development in pre-service PE teachers. Material and methods: The study included data collected in 2017 from 216 male and 221 female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…On the contrary, it may also become a critical point, when PES teachers/sport coaches' professionalization culture, or the whole education system in fact, imposes "discursive closure" in terms of morality, gender discourse [64], or lack of skills in critical thinking. It also may be that the problem is related to the MCL or quality of training of PE teachers/sport coaches as role models themselves [22]. Sanderse [65] signifies that role modelling is rarely used as an explicit teaching method, and only a very small percentage of school students consider teachers as role models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, it may also become a critical point, when PES teachers/sport coaches' professionalization culture, or the whole education system in fact, imposes "discursive closure" in terms of morality, gender discourse [64], or lack of skills in critical thinking. It also may be that the problem is related to the MCL or quality of training of PE teachers/sport coaches as role models themselves [22]. Sanderse [65] signifies that role modelling is rarely used as an explicit teaching method, and only a very small percentage of school students consider teachers as role models.…”
Section: Discussionmentioning
confidence: 99%
“…Henkel and Eearls [21] found that these agents of a child's moral development are, on average, less developed in their moral reasoning capacities than most of their peers with a similar educational background and age. The latest research by Bronikowska and Korcz [22] indicates a problem-78% of PE major students at university were classified as having low MCL themselves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research study also employed a tool proposed by the authors, namely the Factors of Moral Influence Scale [59], among which the following factors deemed to have a significance in the development of one's moral competence were distinguished, particularly: Religion, school, education, parents, Physical Education teacher, sport coach, peers, and media. This tool was constructed on the basis of the 5-point Likert scale of the following ranking, where 1 means 'not important' and 5 means 'very important', and concerned the question 'Who/what has the greatest influence on your moral competence?'…”
Section: Toolsmentioning
confidence: 99%
“…Professionals working with children and youths in area of PA should present the highest standards themselves first. A study on over 440 PE students from all studying years [32] revealed that almost 80% of them presented a very low level of moral competences and the lowest value on the influence scale was attributed to PE teachers. So we wondered whether it was a problem connected to the study programme or earlier PA experiences, and therefore it was interesting to investigate the situation with the newly recruited first year freshmen, because the students' moral consistency might be a crucial factor for the quality of teaching moral education through PE and school sport to the youths.…”
Section: Introductionmentioning
confidence: 99%